Enhanced hydrogen production with carbon storage by olivine alteration in CO2-rich hydrothermal environments. (March 2019) - Wang, Jiajie; Watanabe, Noriaki; Okamoto, Atsushi; Nakamura, Kengo; Komai, Takeshi
Graphical abstract: Highlights: Enhanced H2 production and simultaneous CO2 storage from olivine alteration was realized under hydrothermal conditions. Higher concentration of NaHCO3 promoted olivine consumption and suppressed Fe(II)-bearing brucite generation. Under alkaline conditions, the control of brucite generation is a key point to enhance H2 generation. Abstract: Here we report a novel experimental study on simultaneous hydrogen (H2 ) production and CO2 storage. A high concentration of NaHCO3 (source of CO2 ) is utilized to promote H2 generation from olivine (Mg, Fe)2 SiO4 ) hydration, and then CO2 is reduced to formic acid (HCOOH) or sequestrated in magnesite (MgCO3 ) in a hydrothermal system. The effects of NaHCO3 concentration (0–1.0 mol/L) and initial pH (8–11) on H2 production and CO2 storage were experimentally lab-scale tested at 300 °C. Both reaction pathways and reaction rates changed with variation of the reaction conditions. Under CO2 -rich conditions, olivine consumption was promoted with the absence of Fe(II)-bearing brucite (Mg, Fe(OH)2 ), by which more Mg and Fe ions were released. Thus, the production of H2 and carbonation processes were significantly accelerated. The highest H2 generation rate reached 3.13 mmol/kgolivine ·h, which is more than 15 times higher than previously reported. The HCOOH yield was 129.1 mmol/kgolivine and magnesite ((Mg, Fe)CO3 ) generation reached a maximum of 19.2 wt% in 72 h. The enhancement of H2 production at lower pH is primarily attributed to the presence of HCO3 −, rather than the pH changes caused by NaHCO3 addition. The system proposed here has significant potential to be applied at the field-scale.